2021
DOI: 10.1038/s41467-021-26630-z
|View full text |Cite
|
Sign up to set email alerts
|

Mouse strain-specific polymorphic provirus functions as cis-regulatory element leading to epigenomic and transcriptomic variations

Abstract: Polymorphic integrations of endogenous retroviruses (ERVs) have been previously detected in mouse and human genomes. While most are inert, a subset can influence the activity of the host genes. However, the molecular mechanism underlying how such elements affect the epigenome and transcriptome and their roles in driving intra-specific variation remain unclear. Here, by utilizing wildtype murine embryonic stem cells (mESCs) derived from distinct genetic backgrounds, we discover a polymorphic MMERGLN (GLN) eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…As such, they potentially contribute to the specie-specific characteristics of TESCO activity. In the same line, several studies have shown that TEs are highly heterogeneous between mouse strains (Nellaker et al, 2012;Jung et al, 2023) that can modify gene expression (Zhou et al, 2021) and chromatin dynamics (Ferraj et al, 2023). Therefore, we can speculate that strain-specific TEs could be involved in the sensitivity of a C57BL/6J background to sex reversal (Eicher et al, 1982;Eicher et al, 1996;Munger et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…As such, they potentially contribute to the specie-specific characteristics of TESCO activity. In the same line, several studies have shown that TEs are highly heterogeneous between mouse strains (Nellaker et al, 2012;Jung et al, 2023) that can modify gene expression (Zhou et al, 2021) and chromatin dynamics (Ferraj et al, 2023). Therefore, we can speculate that strain-specific TEs could be involved in the sensitivity of a C57BL/6J background to sex reversal (Eicher et al, 1982;Eicher et al, 1996;Munger et al, 2009).…”
Section: Discussionmentioning
confidence: 92%
“…As such, they potentially contribute to species-specific characteristics of TESCO activity. In the same line, several studies have shown that TEs are highly heterogenous between mouse strains (Jung et al 2023, Nellaker et al 2012) that can modify the genes expression (Zhou et al 2021) and chromatin dynamic (Ferraj et al 2023). Therefore, we can speculate that strain-specific TEs could be involved in the sensitivity of C57BL/6J background to sex reversal (Eicher et al 1996, Eicher et al 1982, Munger et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings related to TEVs have limitations in translational research due to the influence of polymorphic ERVs on intra-species divergence [143]. To address this challenge, the innovation of sequencing technologies, such as long-read sequencing, has identified nearly twice as many new TEVs, some of which are associated with phenotypic differences.…”
Section: Discussionmentioning
confidence: 99%